Identifikasi dan Analisis Senyawa Kimia pada Ekstrak Daun Murbei (Morus alba) Melalui Skrining Fitokimia dengan Metode Spektrofotometer - Wati, Dwi Kartika; Achyar, Zhahrotun Khofifah Nur; Aziza, Nur; Mudzakaroh, Luluk; Pratiwi, Lidia Wahyu; Paramitha, Armanda Bella; Ramadhan, Majida; Nafisa, Nafisa; Mahyantika, Seftya (Biogenesis: Jurnal Ilmiah Biologi, 2024)
Mulberry leaves (Morus alba Linn.) are a plant whose potential has been widely studied because it contains phytochemical compounds such as flavonoids and phenols which have various health benefits. This plant belongs to the Moraceae family and has the characteristics of a woody trunk, branches and brown bark with a height of between 5 and 10 meters, has oval or heart-shaped leaves with tapered tips, and has oval-shaped fruit that is black when ripe. This research aims to analyze chemical compounds in mulberry leaf extract (Morus alba L.) using spectrophotometric methods. Phytochemical screening showed positive results for flavonoids (Shinoda and NaOH test), alkaloids (Wagner and Dragendorff test), tannins (Braymer's solution and base) test, and steroids (Salkowski test). UV-Vis spectrophotometric analysis at a wavelength of 200-800 nm shows maximum absorption at 786 nm for the 10-2 dilution sample. Analysis of total flavonoid content using standard quercetin showed concentrations of 50.06 mg/g and 52.87 mg/g for the 1000 ppm and 500 ppm samples, respectively. The extract yield was 29.086%, with a water content of 4.415% and an ash content of 0.1%. These findings indicate that mulberry leaf extract contains various bioactive compounds with potential pharmacological properties, especially flavonoids which can be useful for medicinal applications.